Implementasi Dekolonisasi Budaya dalam Pembangunan Perdamaian - Ismoyo, Petsy Jessy (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Gender diversity is not limited to essentialist gender paradigms based on binary gender identities. In fact, various gender identities embedded in indigenous beliefs and culture have emerged as a result of various social, cultural and political factors. One such example is the Bissu community among the Bugis peoples of South Sulawesi. Using an indigenous queer perspective on peacebuilding, this article challenges the dominant gender binary paradigm, promoting tolerance and inclusivity. This perspective contributes to the understanding of human rights at the global community level by emphasizing the importance of decolonization, intersectionality, and the recognition of diverse identities based on the experiences of each group. The implementation will be carried out through a model of peace building for indigenous queers through the Sere Bissu Training in collaboration with the Project Budaya Bone, Kerukunan Waria-Bissu Bone (KWRB), the Bone Regency Tourism Office, and the Bone Regency Cultural Office in 2022 in Bone Regency, South Sulawesi. Sere Bissu training has successfully ensured active participation of Bissu group, developed skills and resources within the community, and disseminated the importance of cultural identity and indigenous belief that can lead to Bissu community advocacy and reconciliation. This training has become a peacebuilding model for revitalizing and supporting the Bissu community.